PEMBERDAYAAN PEREKONOMIAN KELOMPOK PETANI LELE MELALUI PROGRAM “PAMAN LELE JEPRET” DI DESA MANARUWI, BANGIL, PASURUAN - M Daimul Abror (LPPM Universitas Yudharta Pasuruan, 2018)
Manauwi Village is one of the villages in district of Bangil, Pasuruan Regency. Manaruwi village has good potential in the field of freshwater fisheries, especially catfish. In order to empower rural communities in the field of fisheries, community assistance was carried out in the